Pola Asuh Ayah Kepada Anak Laki-Lakinya Berdasarkan Lagu Poda - Mutiara, Mutiara Hendri (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Poda (advice) is a gentle, sincere, and motivating expression this is the essence of poda. Most of the time, advice reflects a well-meaning intention for the well-being of the person being advised. The purpose of giving advice is to remind someone that every action carries consequences. Prohibitions, commands, or encouragements regarding certain actions are forms of advice. This article aims to examine how significant a father’s advice is to a child who is leaving for overseas or living away from home, particularly within the Batak Toba cultural context. This study uses a qualitative approach with content analysis of the lyrics in the Poda song. The results indicate that the song is rich in moral, spiritual, and cultural values that contribute to shaping a child’s character especially in maintaining identity, responsibility, and harmonious relationships with both parents and God while away from home. Poda serves as a medium for intergenerational transmission of noble values, which not only influence the child’s behavior but also strengthen emotional and spiritual bonds between parent and child..